Significado de la alimentación y del complemento alimentario MANA en un grupo de hogares de Turbo, Colombia (2012)
ABSTRACT: to understand meanings attributed to diet and food supplement from a group of families beneficiaries of MANA’s food complementary program in Turbo, Antioquia-Colombia. The MANA program provides fortified cookies and powdered milk. Methodology: this is a qualitative study. The focalized ethnography method was used as a methodological approach; which involved participant observation, interviews and focus groups. The obtained information was coded and categorized. Results: MANA’s food complementary program mitigates hunger. It is because it is provided to low income families. MANA’s food complementary program contributes to change habits related with food intake in children.